Analisis Penentuan Perawatan Mesin Roll Table 5Q Dengan Metode Reliability Centered Maintenance (RCM) II Dan Life Cycle Cost (LCC) Di PT XYZ - Widya Amelia Krisnanda; Endang Pudji Widjajati (International Forum of Researchers and Lecturers, 2023)
Machine maintenance must be carried out as a support for the reliability of a machine so that the production system can run smoothly to meet production needs. The fundamental problem of this study is in PT XYZ with the Roll Table 5Q machine, which frequently experiences sudden damage caused by critical components. The goal of the study was to determine the maintenance time interval of the 5Q Roll Table machine, the optimal age of the machine, and the number of mechanics based on the minimum total maintenance cost in an effort to improve the reliability of the machine using the Reliability Centered Maintenance (RCM) II methods and Life Cycle Cost (LCC) methods. From the results of research for critical components As Roll Table obtained interval value of 331 hours / 13 days once a year with the selection of action is Scheduled restoration task and for Bearing components obtained interval value of 109 hours/5 days once a year with the selection of action is Scheduled on-condition task. From the calculation of the total life cycle cost of Rp. 3,720,459,386 with the optimal number of mechanics on the Roll Table machine as many as 3 mechanics with an efficiency level of 9.63% with an optimal age for the Roll Table machine 5Q is 12 years.